Long‐Term Clinical Outcomes of Treatments for In‐Stent Chronic Total Occlusions: A Real‐World Study Based on Different Strategies of Revascularization - Zhuoran Yang; Jiasheng Yin; Yiqing Hu; Li Zhu; You Zhou; Yaqi Zhang; Nirupama Krishnamurthi; Jieyu Jiang; Wenxian Zhou; Nitin Barman; Hao Lu; Junbo Ge (MedComm – Future Medicine)
ABSTRACT Coronary artery disease (CAD), the most common panvascular disease, can progress to chronic total occlusion (CTO). Drug‐eluting stent (DES) is one of standard CAD treatments, but in‐stent restenosis leading to CTO is challenging, with unclear optimal management. The efficacy of drug‐coated balloons (DCB) for treating DES‐related in‐stent chronic total occlusion (IS‐CTO) is undetermined. In this single‐center retrospective cohort study of 198 patients with IS‐CTO post‐DES, 3‐year outcomes of DCB, DES, and plain old balloon angioplasty (POBA) were compared, focusing on target vessel failure (TVF). DES showed the lowest TVF rate (DCB vs. DES vs. POBA: 31.8% vs. 17.1% vs. 51.6%, p < 0.01), mainly due to fewer revascularizations. Notably, the difference in TVF between DCB and DES became more apparent after the first year. DCB was an independent risk factor for late TVF (HRadj = 6.51, 95% confidence interval [CI] = 2.45–18.84, p < 0.01), whereas POBA for early TVF compared to DCB (HRadj = 5.01, 95% CI = 1.36–18.42, p = 0.02). While POBA‐treated patients exhibited a higher target vessel myocardial infarction rate, the death rates were comparable across all cohorts. In conclusion, DES showed the lowest 3‐year TVF rate, making it the most effective treatment for IS‐CTO compared to DCB and POBA.